Migrating to Azure Transforming Legacy Applications into Scalable Cloud-First Solutions - Garverick, Josh (Apress, 2018)
Design an enterprise solution from scratch that allows the migration of a legacy application. Begin with the planning and design phase and be guided through all the stages of selecting the architecture framework that fits your enterprise. Join Microsoft MVP Josh Garverick as he addresses all major areas of design and implementation-application, infrastructure, data, security, and deployment-while leveraging the power and tools of Visual Studio Team Services (VSTS) to bring DevOps to the forefront. With an emphasis on principles and best practices of enterprise design, you will discover how to recognize existing patterns within the legacy platform and to identify potential risks, bottlenecks, and candidates for automation. What You'll Learn: Accurately and completely capture baseline information about a legacy system Leverage enterprise patterns for constructing next-generation platforms in the cloud Design, plan, and implement deployment pipelines to enable continuous delivery Identify and implement cloud-based platform components to reduce total cost of ownership Understand testing and validation: iterative component authoring, monitoring, deployment, and performance Price and perform capacity planning for cloud-based infrastructure and workloads This book is for enterprise architects and IT professionals who are required to keep legacy applications relevant in today's cloud-first world. Josh Garverick is a Microsoft MVP and a seasoned IT professional with more than 15 years of enterprise experience, specializing in Application Lifecycle Management. He is currently involved with DevOps and architecture projects, focusing on software architecture and enterprise needs. Josh is a Visual Studio ALM Ranger, providing guidance, practical experience, and solutions to the developer community. .